Transarterial Embolotherapy Combined with Chemotherapy Versus Immunotherapy for Breast Cancer Liver Metastasis - Bommineni, Maanasa; Annie, Frank; Bryce, Yolanda; Deipolyi, Amy R. (Journal of Clinical Interventional Radiology ISVIR, 2025)
Breast cancer liver metastases (BCLMs) are common and associated with poor prognosis despite systemic treatments. This study compared overall survival (OS) and treatment outcomes of transarterial radioembolization (TARE) and transarterial chemoembolization (TACE) for BCLM, including the impact of their combination with immunotherapy or chemotherapy.This retrospective cohort study used a large multicenter database, TriNetX, which aggregates anonymized electronic medical records from 68 health care organizations in the United States, and included patients with BCLM who underwent TARE (n = 334) or TACE (n = 84) between January 2016 and July 2024, after progressing despite one, two, or three lines of systemic therapy. TARE or TACE was performed alone or in combination with chemotherapy or immunotherapy. The primary outcome was OS, and secondary outcomes included liver function changes and adverse events. Kaplan–Meier and propensity score-matched analyses were performed.Median OS was significantly longer after TARE (36 months) than TACE (25 months; p = 0.04). Immunotherapy/TARE showed the longest OS (38 months), followed by immunotherapy/TACE (36 months; p = 0.03), chemotherapy/TARE (33 months; p = 0.05), and chemotherapy/TACE (30 months; p = 0.04). TACE was associated with higher postprocedural liver enzyme elevations and greater rates of adverse events compared with TARE.In this large retrospective study, TARE was associated with superior survival and better tolerability compared with TACE in BCLM patients. Combination with immunotherapy further improved outcomes, suggesting potential synergy. These findings highlight the need for prospective studies to evaluate the role of TARE and immunotherapy in BCLM treatment.
Keywords: breast cancer liver metastasis; radioembolization; chemoembolization